Qualitative content analysis of complementary topical therapies used to manage diabetic foot in Jordan - Abu-Qamar, Ma'en; Wilson, A. (African Networks on Ethnomedicines, 2012)
In order to alleviate diabetic foot problems, patients sometimes seek complementary therapies outside theprofessional context. This paper describes the use of complementary remedies as a topical treatment for diabetic foot ulcersamong Jordanians. Qualitative content analysis was used to analyse written responses of 68 patients with diabetes who haveused complementary therapies to treat diabetic foot problems. These 68 persons represented a subgroup of the studypopulation surveyed using a questionnaire, to the effect of investigating diabetic foot treatments provided in Jordan.Informants were recruited from eight healthcare facilities established in the southern part of Jordan plus from one hospitalestablished in the Jordanian capital. The study was approved by the Boards of Ethics of the participating healthcare facilities.Content analysis yielded the category “Complementary Therapies Used”, which included a range of household items (oliveoil, sesame oil, honey, and vinegar), and also some indigenous Jordanian herbs (Wormwood, Myrrh, Caper, and Hennaamong others). The remedies were used either as a monotherapy or as mixtures, to the common goal of treating diabetic footproblems. Other interventions like Al-cowy were also sought from traditional healers. Educational campaigns are required toincrease the awareness of patients and their families on possible hazards of unwise complementary therapy use. The decisionson the use of such therapies should be made in agreement with the attending healthcare professionals.